Analisis Pengaruh Islamicity Performance Index Terhadap Profitabilitas Dengan Intellectual Capital Sebagai Variabel Moderasi - Murtadho Kesuma; Nafis Irkhami (Jurnal Akuntansi dan Keuangan Kontemporer (JAKK), 2021)
This study aims to determine the effect of the Islamicity Performance Index on Profitability with Intellectual Capital as a Moderation Variable in Islamic Commercial Banks for the 2015-2019 Period. This type of research is quantitative research using Moderate Regression Analysis (MRA) as data analysis and using secondary data in the form of panel data. The data  hat has been obtained is then processed using the E-views 9 application tool. Based on the results of this study it shows that partially the Profit Sharing Ratio (PSR) variable has a positive and insignificant effect on profitability, Zakat Performance Ratio (ZPR) has a negative and insignificant effect on profitability. Directors Employees Welfare Ratio (DEWR) has a positive and significant effect on profitability, while Islamic Income vs Non-Islamic Income Ratio (IIcR) has no significant negative effect on profitability. Intellctual Capital is able to moderate the effect of Zakat Performance Ratio (ZPR) but unable to moderate the effect of Profit Sharing Ratio (PSR), Directors Employees Welfare Ratio (DEWR), and Islamic Income vs Non-Islamic Income Ratio (IIcR) on profitability.